Factors influencing islamic unit trust decision among community in Kota Bharu / Nortasha Sopiara Nusi - Nusi, Nortasha Sopiara (2018)
Islamic unit trust offers the opportunity to investors to invest in a diversified portfolio of shares and securities that are comply with Shariah principles. Over the past decades, the growth of Islamic unit trust industry in Malaysia has been tremendous. Islamic unit trust fund is among the fastest growing investment products in Malaysia. Thus, it is vital to investigate the factors that influence an investor to invest in Islamic unit trust fund. As mentioned by Barberis & Thaler (2003), it is important to understand the decision-making factor of the investors. As a result, it can help asset management companies to strategize in attracting the investors based on the significant factors with an Islamic unit trust investment decision. Research objective of this study is to study the factors that influence the Islamic Unit Trust decision among the Community in Kota Bharu Kelantan. The target population of this study is addressed to the community in Kota Bharu that visit Amanah Saham Nasional Berhad Kota Bharu. A total 273 set of survey questionnaires will be personally distributed and collected from the respective respondents. The items in the questionnaire were adopted and combined from several previous studies. There are four factors (independent variables) in this study; product knowledge, religiosity, information sources and Islamic financial literacy. It is expected from this study, product knowledge, religiosity, information source, and Islamic financial literacy factors significantly give the impact to Islamic unit trust decision making among Community in Kota Bharu Kelantan.